Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

Molecular analysis of insecticide resistance mutation frequencies in five cockroach species from Korea - Hyun Kyu Shin; Susie Cho; Gang Chan Lee; Do Eun Lee; Heung Chul Kim; In Yong Lee; Chung Hyun Ko; Soon-il Kim; Seong Soo Kim; Ju Hyeon Kim; Si Hyeock Lee (Pesticide Biochemistry and Physiology, 2025)

2,7-Phloroglucinol-6,6′-bieckol from Ecklonia cava ameliorates nanoplastics-induced premature endothelial senescence and dysfunction - Hwan-Hee Sim; Saugat Shiwakoti; Ji-Hyeok Lee; In-Young Lee; Yejoo Ok; Han-Kyu Lim; Ju-Young Ko; Min-Ho Oak (Science of The Total Environment, 2024)

The novel catabolic pathway of 3,6‐anhydro‐ L ‐galactose, the main component of red macroalgae, in a marine bacterium - Eun Ju Yun; Saeyoung Lee; Hee Taek Kim; Jeffrey G. Pelton; Sooah Kim; Hyeok‐Jin Ko; In‐Geol Choi; Kyoung Heon Kim (Environmental Microbiology, 2015)
Summary The catabolic fate of the major monomeric sugar of red macroalgae, 3,6‐anhydro‐ L ‐galactose ( AHG ), is completely unknown in any organisms. AHG is not catabolized by ordinary fermentative microorganisms, and it hampers the utilization of red macroalgae as renewable biomass for biofuel and chemical production. In this study, metabolite and transcriptomic analyses of V ibrio sp., a marine bacterium capable of catabolizing AHG as a sole carbon source, revealed two key metabolic intermediates of AHG , 3,6‐anhydrogalactonate ( AHGA ) and 2‐keto‐3‐deoxy‐galactonate; the corresponding genes were verified in vitro enzymatic reactions using their recombinant proteins. Oxidation by an NADP + ‐dependent AHG dehydrogenase and isomerization by an AHGA cycloisomerase are the two key AHG metabolic processes. This newly discovered metabolic route was verified in vivo by demonstrating the growth of E scherichia coli harbouring the genes of these two enzymes on AHG as a sole carbon source. Also, the introduction of only these two enzymes into an ethanologenic E . coli strain increased the ethanol production in E . coli by fermenting both AHG and galactose in an agarose hydrolysate. These findings provide not only insights for the evolutionary adaptation of a central metabolic pathway to utilize uncommon substrates in microbes, but also a metabolic design principle for bioconversion of red macroalgal biomass into biofuels or industrial chemicals.

Expression of a recombinant chimeric protein of human colorectal cancer antigen GA733-2 and Fc fragment of antibody using a replicating vector based on Beet curly top virus in infiltrated Nicotiana benthamiana leaves - Kyung Il Kim; Ha Young Chung; Ki Hyun Yoo; Jong-Hwa Park; Hyun Ho Lee; Yeon Ju Soek; Ki Sung Ko; Hyung Sik Kang; Kyung Jin Lee; Doo-Byoung Oh; Young Hee Joung; In Sik Chung (Plant Biotechnology Reports, 2012)

Stabilization of the As-contaminated soil from the metal mining areas in Korea - Myoung-Soo Ko; Ju-Yong Kim; Sunbeak Bang; Jin-Soo Lee; Ju-In Ko; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2012)

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6 - Jang Hoon Lee; Kyung Cheol Ma; Sug Ju Ko; Beom Ryong Kang; In Seon Kim; Young Cheol Kim (Current Microbiology, 2011)